Hello, Mrs. Piggle-Wiggle - MacDonald, Betty Bard.frey50; Knight, Hilary (New York, NY : HarperTropphy, 1985)
A woman with a magic way of curing children's bad habits tries her hand with a bully, a whisperer, and a slowpoke and formulates cures for a show-off and a crybaby.
73552
Keywords: Behavior -- Fiction; Humorous stories; Short stories